Constructing a new framework for rural development - Milone, Pierluigi; Ventura, Flaminia; Ye, Jingzhong (Bingley, U.K. : Emerald, 2015)
This volume seeks to answer modern questions and concerns regarding peasants, their production techniques, and their links to wider society. In the past, peasants and their seemingly simple production models have been criticized for being unable to fully meet the needs of modern society, especially when it comes to world hunger, food quality, and sustainability. However, often neglected is the myriad of new initiatives that alter the way food is produced and marketed. New âpeasant marketsâ are created everywhere and new products and services abound. This volume argues that these initiatives represent âseeds of transitionâ; they are the âsproutsâ out of which new socio-technical modes for organizing production and marketing emerge â âsproutsâ that, taken together, can be summarized as ârural developmentâ. This book critically discusses these new practices and the actors engaged in them. In doing so, it deals with several countries in three different continents (Asia, South America and Europe). It proposes new concepts and approaches for a better understanding of the re-emergence of peasants as indispensable part of modern societies.
Introduction / Pierluigi Milone, Flaminia Ventura, Jingzhong Ye -- Rural development : actors and practices / Jan van der Ploeg, Jingzhong Ye, Sergio Schneider -- Activities, actants and actors : theoretical perspectives on development practice and practitioners / Norman Long -- Is multifunctionality the road to empowering farmers? / Pierluigi Milone, Flaminia Ventura -- Peasant innovation and grassroots action in China / Jingzhong Ye, Huiyang Fu -- Seeds and sprouts of rural development : innovations and nested markets in small scale on-farm processing by family farmers in south Brazil / Sergio Schneider, Marcio Gazolla -- Hidden treasures : reconnecting culture and nature in rural development dynamics / Paulo F. Petersen -- Rural development from the grassroots : twenty years of the EU "leader approach" / Laurent Van de Poele -- The distinctiveness of rural development practices in north west Europe / Rudolf Van Broekhuizen ... [et al.] -- Towards the characterization of actors engaged in rural development processes in the north west of Europe / Henk Oostindie ... [et al.] -- Weaving the institutional market : the politics of food production in land reform settlements in Brazil / Claudia Schmitt -- Revisiting evolving webs of agri-food and rural development in the UK : the case of Devon and Shetland / Jessica Paddock, Terry Marsden -- Conclusion : reproducing future in rural area / Pierluigi Milone, Flaminia Ventura, Jingzhong Ye.
Print version record
Keywords: Social Science -- Sociology -- Rural; Rural communities; Sociology: work & labour; Rural development; Community development